1997
DOI: 10.1111/j.1398-9995.1997.tb01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mosquito saliva‐specific IgE antibodies by capture ELISA

Abstract: We developed an IgE-capture ELISA and measured mosquito saliva-specific IgE antibodies in 27 children sensitive to mosquito bites. Children with large 15-min bite wheals had significantly higher (P < 0.0005) mosquito saliva-specific IgE levels than children with small wheals. In the latter group, the saliva-specific IgE level was significantly higher (P = 0.031) than the levels of six infants never exposed to mosquitoes. A positive correlation (r = 0.65; P = 0.0002) was found between the size of the 15-min whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 17 publications
3
29
0
1
Order By: Relevance
“…Elevated serum mosquito saliva-specific IgE has also been detected by immunosorbent assays which include enzyme-linked immunoassays (ELISA) (fig. 1) [2, 5, 20], RAST [18], and the UniCap test [21], Western blot [22, 23], and histamine release from basophils [19]in mosquito-allergic or mosquito bite test-positive subjects. There is no doubt that IgE is involved in the pathogenesis of mosquito allergy.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…Elevated serum mosquito saliva-specific IgE has also been detected by immunosorbent assays which include enzyme-linked immunoassays (ELISA) (fig. 1) [2, 5, 20], RAST [18], and the UniCap test [21], Western blot [22, 23], and histamine release from basophils [19]in mosquito-allergic or mosquito bite test-positive subjects. There is no doubt that IgE is involved in the pathogenesis of mosquito allergy.…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…These studies demonstrated that the quantitative evaluation of antibody responses to saliva by enzyme-linked immunosorbent assay (ELISA) could be a useful biomarker for human exposure to Aedes bites. 23,24 IgG4 to Aedes aegypti saliva was associated with intense exposure to Aedes bites. 25 Recently, IgM and IgG responses to Ae.…”
mentioning
confidence: 99%
“…Possibly the naturally acquired immunity by repeated exposure is crucial [17], e.g. IgE and IgG antibodies to allergens of several mosquito species have been found [15, 18]. Typically the levels are highest in children and slowly decrease over time.…”
Section: Systemic Reactions To Arthropodsmentioning
confidence: 99%